Mortality in psoriatic arthritis patients, changes over time, and the impact of COVID-19: results from a multicenter Psoriatic Arthritis Registry (PsART-ID) - DURUÖZ, MEHMET TUNCAY (My University, 2023)
© 2023, The Author(s), under exclusive licence to International League of Associations for Rheumatology (ILAR).Background: This study aimed to assess the mortality of PsA before and during the COVID-19 pandemic. Methods: From the prospective, multicenter PsART-ID (Psoriatic Arthritis Registry-International Database), patients from Turkey were analyzed by linking the registry to the Turkish Cause of Death Registry. The outcome of interest was death from any cause, pre-pandemic (since the onset of registry—March 2014–March 2020), and during the pandemic (March 2020–May 2021). The crude mortality rate and standardized mortality ratio (SMR) were determined. Results: There were 1216 PsA patients with a follow-up of 7500 patient-years. Overall, 46 deaths (26 males) were observed. In the pre-pandemic period, SMR for PsA vs the general population was 0.95 (0.61–1.49), being higher in males [1.56 (0.92–2.63)] than females [0.62 (0.33–1.17)]. The crude mortality rate in PsA doubled during the pandemic (pre-pandemic crude mortality rate: 5.07 vs 10.76 during the pandemic) with a higher increase in females (2.9 vs 8.72) than males (9.07 vs 14.73). Conclusion: The mortality in PsA was found similar to the general population in the pre-pandemic era. The mortality rates in PsA doubled during the pandemic. Whether PsA patients have more risk of mortality than the general population due to COVID-19 needs further studies.Key Points• Decrease in mortality in PsA might be expected with the more effective treatment options and better disease control.• A crude mortality rate is comparable to the general population and not increased until the pandemic.• Currently, there is a 2-fold increase in crude mortality rate possibly due to the COVID-19.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ROMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; RHEUMATOLOGY; Romatoloji; Rheumatology; COVID-19; Mortality; Pandemic; Psoriatic arthritis